Harnessing functional feed additives for sustainable production: the role of Bacillus coagulans and Paenibacillus polymyxa mixture in improving production and health of meat-type quails - Reda, Fayiz M.; Alagawany, Mahmoud; Salah, Ayman S.; Almutairi, Layla A.; Alqahtani, Mohammed A.; Alamoudi, Soha A.; Altuwaijri, Saleh; El-Tarabily, Khaled A.; El-Saadony, Mohamed T. (Frontiers in Veterinary Science, 2025)
IntroductionDespite the widespread interest in using Bacillus spp. as a probiotic in poultry diets, no evidence has been found to support the use of Paenibacillus polymyxa in the diet of Japanese quails. This study examined the effects of supplementing growing Japanese quail with a mixture of Bacillus coagulans and P. polymyxa (Bc+Pp) on their growth performance, antioxidative activity, immunological status, digestive enzymes, caecal microbiota, and blood chemistry.MethodsTwo hundred 1-week-old meat-type quail chicks were divided into four groups at random; five pens, each containing ten birds. These birds were provided with a basic feed as a control group, or a feed diet treated with 0.5, 1.0, and 1.5 mg kg−1 of Bc+Pp mixture (1:1).ResultsAccording to the findings, the growing quail's growth performance was significantly (P < 0.05) enhanced by supplementing the Bc+Pp mixture. Body weight and body weight gain were boosted significantly (P = 0.0002, P = 0.0003) by Bc+Pp mixture supplementation at 5 weeks and 1–5 weeks. In contrast, feed consumption showed a non-significant difference (P = 0.8082) with the treatments within 1–5 weeks. Moreover, the feed conversion ratio was significantly (P < 0.05) boosted (P = 0.0137) with the supplementation of the Bc+Pp mixture. Furthermore, Bc+Pp mixture supplementation provided a significant boost in carcass traits, especially liver, gizzard, and giblet percentage (P = 0.0112, P = 0.0976, and P = 0.0028). The current result showed a significant (P < 0.05) increase in total protein, albumin, and globulin with supplementation of the Bc+Pp mixture. Moreover, the treatment significantly (P < 0.05) reduced total cholesterol, triglycerides, and low-density lipoprotein. Superoxide dismutase, total antioxidant capacity, reduced glutathione, and glutathione peroxidase were significantly (P < 0.05) improved by supplementation of the Bc+Pp mixture. Furthermore, the digestive enzymes were significantly (P < 0.05) improved, and the total bacterial and lactic acid bacteria counts were significantly (P < 0.05) augmented, whereas the counts of Salmonella spp., Escherichia coli, total coliform, and Enterococcus spp. were significantly (P < 0.05) decreased with dietary bacterial mixture treatments.DiscussionIn conclusion, supplementing growing Japanese quail with a mixture of Bc+Pp has a positive impact on their growth performance, antioxidative status, immunological response, digestive enzymes, and caecal microbiota.